Educators’ Perceptions Towards Their Roles and Experiences in Adapting Alternative Assessment - Wan Robiah, Meor Osman; Wan Sofiah, Meor Osman; Rosnah, Mustafa; Nor Hasniah, Ibrahim; Nur Fatihah, Abdullah Bandar (2024)
The use of alternative assessment has gained significant attention in recent years, especially during the COVID-19 pandemic. Traditionally educators rely on written examinations to assess students’ understanding of course content; however, it has become increasingly evident that written examinations alone may not fully capture the breadth and depth of students’ learning. Alternative assessment has been used to provide a more comprehensive evaluation of students’ learning in which students can learn mental skills, develop attitudes and the potential to acquire new physical skills. These three domains of learning are commonly known as Bloom’s Taxonomy (Bloom, 1956) and learning is viewed as a process of human development and growth (Hoque, 2016). The role of educators is critical in deciding and setting alternative assessments to ensure students’ learning captures these domains. Undoubtedly, educators as academic knowledge experts are often prepared for the research role, but they might have had little or no training for the teaching role (Kane, et al., 2002; Minter, 2010) which includes assessing students. Despite the crucial role educators must play, very little is known about educators’ perceptions and experiences regarding alternative assessment. Herein, this study delves into the adaptation of alternative assessment among educators, their perceptions and experiences. This study aims to shed light on the significance of alternative assessment as a means to inform practices in higher education.